MOTIVASI BELAJAR MANDIRI PESERTA DIDIK PADA MATA PELAJARAN PKN SMP NEGERI 2 PULAU MAKIAN (Studi Kasus Desa Malapat Kec. Makian Barat Kabupaten Halmahera Selatan) - Risno Rusdi; Mukhtar Yusuf (Universitas Khairun, 2018)
The formulation of the problem in this study is how the role of the teacher in motivating students' learning in VIII grade SMP Negeri 2 Pulau Makian. The purpose of this study was to determine the role of teachers in fostering learning motivation of eighth grade students of SMP Negeri 2 Pulau Makian Regency of South Halmahera in 2015/2016. The research approach used is qualitative. The research location was SMP Negeri 2 Pulau Makian, Malapat Village, West Makian Subdistrict, South Halmahera Regency, which was held from February to April 2017. The subjects of this study were teachers and students of class VIII of SMP Negeri 2 Pulau Makian with a technique of collecting data through observation, interviews, documentation. The results of this study are then processed and analyzed qualitatively using the theories or opinions of relevant experts. Based on the results of research on the motivation of independent learning of students in Civics education in SMP Negeri 2 Pulau Makian, it was concluded that motivation for independent learning in PKn subjects was to arouse students to learn, give teachings on achievement which students reach later on and form good learning habits. The forms of motivation for independent learning include determining the atmosphere of fun teaching and learning, providing interesting learning material giving gifts to those who excel, giving punishment, to those who commit violations, and giving praise. Factors that influence the motivation of independent learning, namely the lack of attention from parents (father and mother): Parents tend to let their children take care of themselves, and the influence of friends or peers. Friends like to invite negative things, such as skipping and not going to school. Keywords: Motivation, for Independent, Learning Students, PKn Subjects